Energy Benefits of PV-Integrated Dynamic Overhangs for Residential Buildings in Qatar - Moncef Krarti; Mohamed A. Ayari; Farid Touati; Mohammad R. Paurobally (Energies)
This paper summarizes the potential energy efficiency benefits of PV-integrated dynamic overhangs for housing units in Qatar. Specifically, the technology combines two energy benefits of shading effects of reducing air conditioning loads and generating on-site electricity generation. The analysis is performed for a prototypical dwelling unit in Doha, Qatar. Three adjustment frequencies for the positions of the PV-integrated dynamic overhangs are evaluated, including hourly, daily, and monthly. It is found that optimally operated PV-integrated overhangs can substantially reduce the annual electricity needs of the dwelling unit. For instance, southern-oriented PV-integrated dynamic overhangs can lower the annual net energy requirements for the dwelling unit by 69.7% relative to the case with no shading and by 32.2% relative to the case of deploying PV-integrated static overhangs. Higher energy use reductions can be achieved when the overhang depth and window size are increased and when more energy-efficient glazing types are installed.